2023
DOI: 10.1002/eap.2795
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in resource availability shape the competitive balance among non‐native plant species

Abstract: Fluctuating resource availability plays a critical role in determining non‐native plant invasions through mediating the competitive balance between non‐native and native species. However, the impact of fluctuating resource availability on interactions among non‐native species remains largely unknown. This represents a barrier to understanding invasion mechanisms, particularly in habitats that harbor multiple non‐native species with different responses to fluctuating resource availability. To examine the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…This study provides valuable insights into the management of invasive plants in changing environments. Additionally, Tao et al (2023) revealed diverse responses to nutrient pulses among alien species, with certain species gaining advantages while others did not. Importantly, in a community context, nutrient fluctuations promoted the success of advantaged species.…”
Section: Performance Of Successful Iasmentioning
confidence: 99%
“…This study provides valuable insights into the management of invasive plants in changing environments. Additionally, Tao et al (2023) revealed diverse responses to nutrient pulses among alien species, with certain species gaining advantages while others did not. Importantly, in a community context, nutrient fluctuations promoted the success of advantaged species.…”
Section: Performance Of Successful Iasmentioning
confidence: 99%
“…The importance of fluctuating resource availability for non‐native plant invasions has been confirmed by a large number of experimental evidence in terms of nutrients. For example, compared to nutrients supplied constantly, multiple small pluses and a single large pulse strongly increased the ratio of non‐native plants in the native communities (Parepa et al., 2013 ; Tao et al., 2021 ) or promoted non‐native plants growth when they grew individually (Liu & van Kleunen, 2017 ; Tao et al., 2023 ). In addition to nutrients, water is vital for the survival, growth, and reproduction of terrestrial plants (Castillioni et al., 2022 ; Eziz et al., 2017 ; Mojzes et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to human-driven global change, most terrestrial ecosystems are experiencing great fluctuations in resource availability ( Li et al., 2022 ; Tao et al., 2023 ). The fluctuating resource can influence the growth of plants directly by changing the nutrient uptake ( Warren et al., 2003 ), or indirectly by affecting the activities of soil microbes ( Carrero-Colón et al., 2006a ; Carrero-Colón et al., 2006b ), and then subsequently affects the heavy metal uptake of plants.…”
Section: Introductionmentioning
confidence: 99%